Linking CSR and brand performance through customer satisfaction, brand equity and corporate reputation: A mixed methods study of top Pakistani banks - Masood Ul Hassan; Zeeshan Mahmood; Samar Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The basic aim of the study is to examine how and why the phenomenon of brand performance (BP) occurs within the Pakistani banking sector through the direct and indirect relationship(s) of corporate social responsibility (CSR) perceptions with customer satisfaction (CS), brand equity (BE), and corporate reputation (CR).The theoretical lenses of stakeholder and resource-based theories as well as the concept of customer-based brand equity and the expectancy disconfirmation theory are used to develop the conceptual model. Based upon a post-positivist philosophy with a social constructionist ontology, the current study employed the explanatory sequential mixed methods approach. The current study collected data cross-sectionally through the use of a structured questionnaire, and analyzed quantitatively through the PLS-SEM in the first phase, and then followed by qualitative interviews to help explain survey responses. The results firstly found that CSR perceptions have a direct impact on customer satisfaction (CS), followed by corporate reputation (CR), and brand equity (BE). Second, customer satisfaction (CS) affects corporate reputation (CR) and brand equity (BE) directly. Third, brand equity (BE) and corporate reputation (CR) directly impacted brand performance (BP). Finally, customer satisfaction (CS), corporate reputation (CR), and brand equity (BE) emerged as powerful mediators. Theoretical and managerial implications along with limitations and directions for future research have also been discussed.
Keywords: 330; corporate social responsibility; customer-based brand equity; corporatereputation; brand performance; banking sector; Pakistan